(untitled) (American Journal of Islam and Society, 2006)
The anthropological literature on Yemen has had little to say about the class of sadah (plural of sayyid) who dominated the Zaydi imamate in North Yemen from the tenth century until 1962. Gabriele vom Bruck’s account of the sadah, based on interviews and an extended stay in Yemen starting in 1983, includes a wide range of information on perceptions of this class, especially after the 1962 revolution, with an emphasis on how personal identity is established and attitudes about marriage with non-sadah. There is an extensive bibliography of western sources, but little indication of the wide range of relevant Arabic sources available. It should be noted that vom Bruck almost totally ignores the sadah of southern Yemen as well as of the Tihama, although her text sometimes reads as if it were describing a generic class of sadah for Yemen as a whole. The author’s stated goal is “to examine the relationship of experience, social practice, and moral reasoning among the hereditary elite in the context of revolutionary change” (p. 5). Her theoretical focus is on the social process of remembrance as the sadah were forced into new roles after the imamate’s demise. Vom Bruck argues that we should avoid “a monolithic understanding of sayyid as a ‘vessel of charisma’ and ‘paragon of piety’” (p. 250) and suggests that the “descent metaphor” (p. 6) was the “principle self-defining criterion” of the sadah as well as the “core of the Imamate’s political culture.” (p. 6) However, the idiom of descent has also been the defining feature of Yemen’s tribes, so the role of descent per se is less relevant as a distinguishing marker than how the sadah relate to other social categories. Although the relationship with tribesmen is mentioned at several points, it is not analyzed in depth apart from anecdotal evidence. For example, it is highly problematic to label musicians al-akhdam (p. 44), who were actually quite rare in Zaydi towns and villages, a nuanced pariah category. There is little sense of how the sadah fit into actual communities, and no effective integration of the available literature previously published on Yemeni social categories (including Tomas Gerholm’s Market, Mosque, and Mafraj [Stockholm University Press: 1977] and Eduard Glaser’s important late-nineteenth century articles) ...